Predictors of Complications and Unfavorable Outcomes of Minimally Invasive Surgery Treatment in Elderly Patients With Degenerative Lumbar Spine Pathologies (Case Series) - Klimov, Vladimir; Evsyukov, Aleksey; Amelina, Evgeniya; Ryabykh, Sergey; Simonovich, Alexander (Frontiers in Surgery, 2022)
Introduction. The use of minimally invasive surgery (MIS) results in fewer adverse and more improved outcomes. However, the literature data describing the factors increasing the number of complications, reoperation frequency and unscheduled re-hospitalizations in older patients after MIS are contradictory. In this study, a large cohort of patients was investigated for the complications of minimally invasive surgical treatment of degenerative disease of the lumbar spine in older patients. The objective of the study was to determine the predictors of unfavorable outcomes in such patients. Materials and Methods. A cohort of 1013 patients underwent MIS (decompression alone, TLIF, LLIF, ALIF) in 2013-2017. The patient’s average age was 66. The following data were collected: BMI; CCI; presence of postoperative complications according to the Dindo-Clavien classification; unplanned readmission at 90 days; hospital length of stay (LOS); surgical complexity (low, intermediate, and high); surgical time; and risk factors. The cumulative reoperation rate was determined at 5-years follow-up. Results. A total of 256 patients suffered a complication (25,2%), 226 classified as mild (grade I, II, IIIA), and 30 - as severe (IIIB, IVA). Such factors as the surgical complexity, BMI> 30, surgical time, number of operated levels were associated with a significant risk of developing a complication. For patients with and without complications, LOS was 9.3 and 6.3 days, respectively (p< 0,0001), the unplanned readmission rate was 1.3 %. 104 patients underwent 133 revision operations. The 5-year cumulative reoperation rate was 15.2%, and the reoperation index was 12.1%. The CCI had no statistically significant effect on the complication incidence after MIS. A higher risk of complications was found in patients who underwent intermediate-complexity surgery (MIS TLIF) compared with uncompounded (decompression alone) and more complex (MIS LLIF, MIS ALIF) surgical procedures (p <0.001 and p = 0.001, respectively). Conclusion. A register of postoperative complications is an important tool for health quality assessment and choosing the best surgical option that helps to establish measures to reduce such complications. Using MIS for the treatment of elderly patients reduces the number of severe complications.